2015
DOI: 10.15587/1729-4061.2015.42127
|View full text |Cite
|
Sign up to set email alerts
|

Substatiation of truck selection in terms of minimizing psychophysiological stress on a driver

Abstract: С . І . Ч е б е р я ч к оКандидат технічних наук, доцент Кафедра аерології і охорони праці* Е-mail: sihc@yandex.ua *Державний вищий навчальний заклад «Національний гірничий університет» пр. Карла Маркса, 19, м. Дніпропетровськ, Україна, 49005 Обґрунтовано вибір ефективного вантажного автомобіля за допомогою методу профілів. Проаналізовані техніко-експлуатаційні, ергономічні, динамічні, екологічні та силові властивості транспортних засобів. Розроблена методика для прийняття управлінського рішення з оновлення ру… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The proposed solutions provide, first of all, the elimination of the main causes that increase the likelihood of the development of occupational diseases. In addition, if it is impossible to achieve the desired level of ER, appropriate steps are developed either to replace the type of truck [32], or to choose another route [33], or to transfer the worker to another job. All the given recommendations are offered on the basis of a thorough study of the identified dangerous cells (Table 5), which allows to clearly identify the weak points of the technological process.…”
Section: Discussion Of the Results Of The Ergonomic Risk Assessmentmentioning
confidence: 99%
“…The proposed solutions provide, first of all, the elimination of the main causes that increase the likelihood of the development of occupational diseases. In addition, if it is impossible to achieve the desired level of ER, appropriate steps are developed either to replace the type of truck [32], or to choose another route [33], or to transfer the worker to another job. All the given recommendations are offered on the basis of a thorough study of the identified dangerous cells (Table 5), which allows to clearly identify the weak points of the technological process.…”
Section: Discussion Of the Results Of The Ergonomic Risk Assessmentmentioning
confidence: 99%